Case Report: Nerve Root Entrapment Due to Epidural Fibrosis in a Patient With Failed Back Surgery Syndrome: Value of 2-18F-Fluorodeoxyglucose Simultaneous Positron Emission Tomography-Magnetic Resonance Imaging - Tsai, Yueh-Hsun; Huang, Guo-Shu; Tang, Chi-Tun; Chang, Wei-Chou; Hsu, Yi-Chih (Frontiers in Medicine, 2022)
Failed back surgery syndrome (FBSS) is a highly prevalent condition in patients after spine surgery. Although magnetic resonance imaging (MRI) is the gold standard for the diagnosis of epidural fibrosis, it is sometimes difficult to determine if epidural fibrosis contributes to radiculopathy. Herein, we share our experience in locating radiculopathy lesions using simultaneous positron emission tomography (PET)/MRI. 2-[18F]-FDG (18F-fluorodeoxyglucose) simultaneous PET/MRI maps of body glucose metabolism detected using PET can be used to correlate anatomical details provided by MRI to offer a very clear picture of neural inflammation due to extensive epidural fibrosis. More applications of 2-[18F]-FDG simultaneous PET/MRI in low back pain and other musculoskeletal diseases should be further investigated in the future.